Peran Pasar Modal Syari’ah Dalam Perkembangan Perekonomian Di Indonesia - Dewi Khayyirah Novrianti; Herlina Yustati (At-Thariqah: Jurnal Ekonomi, 2024)
This research was conducted to find out whether there is an influence of the Shariah capital market on economic growth in Indonesia. The capital market provides its services by bridging the relationship between capital owners (investors) and fund borrowers (issuers). The method used in this research is qualitative analysis with descriptive analysis and using the literature method by collecting, reading and recording literature studies related to the subject being studied. In conclusion, the sharia capital market is defined as a capital market that applies the principles of sharia in economic transaction activities and is free from prohibited things such as usury, gambling and speculation